A new dallasiellid shark from the lower Campanian (Upper Cretaceous) of Sweden. (3rd April 2022) - Siversson, Mikael; Cederström, Peter; Ryan, Helen E.
ABSTRACT: Examination of isolated shark teeth from the uppermost lower Campanian Gonioteuthis quadrata scaniensis Zone of southern Sweden revealed the presence of a rare, previously undescribed lamniform shark. The unusually small-sized anterior teeth, variable presence of a short and shallow median groove, cusplet shape and outline of posterior teeth indicate a dallasiellid affinity and the species is formally described as Dallasiella brachyodon sp. nov. It is the youngest record of dallasiellids and adds to the extraordinarily high diversity of lamniform sharks in the uppermost lower Campanian of the Kristianstad Basin. Over its 18 Ma range, Dallasiella appears to have increased in body size and developed teeth with relatively broader cusps, indicating enhanced capabilities for tackling larger prey.